The turn of the key [large type] - Ware, Ruth (Thorndike Press large print core, 2019)
Rowan Caine stumbles across a lucrative job as a live-in nanny for a picture-perfect family in the Scottish Highlands. What she doesn't know is that she's stepping into a nightmare that will end with a child dead and herself in prison awaiting trial for murder. Writing to her lawyer from prison, she struggles to explain the events that led to her incarceration. She knows she's made mistakes, and she admits that she lied to obtain the post, and that her behavior toward the children wasn't always ideal. She's not innocent, but she maintains she's not guilty, at least not of murder.